Food processing : - Ramaswamy, Hosahalli (CRC Press, 2006)
In a textbook format for an undergraduate course in food processing, Ramaswamy (food science, McGill U., Montreal-Macdonald) and Marcotte, a chemical engineer working in food science, address the basic principles and applications for major processing techniques of commercial importance. They consider both science and engineering aspects, highlight the chemical and microbiological basis of food preservation, and describe the mathematical basis for modeling and processing applications. The primary focus is on thermal processing, freezing, and dehydration.